Increasing Al-Qur'an Literacy Through Community Based Research - Sopian Sinaga; Ayu Lestari; Siti Annisa; Sopia Rahmi; Ummi Fadila; Widya Sistika (ASSUNNAH PRESS, 2023)
The low ability of the community in Asam Jawa village, Torgamba sub-district, Labuhan Batu Selatan district in terms of reading the Al-Qur'an. Recitation of the Qur'an that is not in accordance with the place where the letters come out (makharijul letters) and the laws of tajwid. Then do not understand the meaning or interpretation of what is read from the Qur'an. The above has encouraged KKNT(Kuliah Kerja Nyata Tematik) Students to channel the knowledge learned to the community through Thematic Community Service activities. The KKNT activities carried out are an effort to increase Al-Qur'an literacy among mothers and children by introducing hijaiyyah letters, makhraj letters and increasing understanding of the Qur'an. KKNT is held in the month of Ramadan to take advantage of the momentum of Ramadan when the majority of Muslims are enthusiastic about worshipping and studying the Qur'an. The KKNT method used to achieve the expected goals uses the Community Based Research (CBR) method. This method has four stages: laying basic principles, research planning, data collection and analysis, and action on findings. The results of this activity show that the quality of reading the Qur'an among children is still low due to their lack of basic knowledge and their lack of discipline in participating in existing activities. As for mothers, there were significant results in improving their reading skills and comprehension. This is supported by enthusiasm, high motivation to learn, and discipline in following the study. It can be concluded that adult students who are active and have basic knowledge find it easier and faster to understand the lessons being delivered.